Insertion element analysis and mapping of the Pseudomonas plasmid alk regulon. - Fennewald, M (1979)
We characterized and mapped new mutations of the alk (alkane utilization) genes found on Pseudomonas plasmids of the Inc P-2 group. These mutations were isolated after (i) nitrosoguanidine mutagenesis, (ii) transposition of the Tn7 trimethoprim and streptomycin resistance determinant, and (iii) reversion of polarity effects of alk::Tn7 insertion mutations. Our results indicate the existence of two alk loci not previously described--alkD, whose product is required for synthesis of membrane alkane-oxidizing activities, and alkE, whose product is required for synthesis of inducible membrane alcohol dehydrogenase activity. Polarity of alk::Tn7 insertion mutations indicates the existence of an alkBAE operon. Mapping of alk loci by transduction in P. aeruginosa shows that there are at least three alk clusters in the CAM-OCT plasmid--alkRD, containing regulatory genes; alkBAE, containing genes for specific biochemical activities; and alkC, containing one or more genes needed for normal synthesis of membrane alcohol dehydrogenase. The alkRD and alkBAE clusters are linked but separated by about 42 kilobases. The alkC cluster is not linked to either of the other two alk regions. Altogether, these results indicate a complex genetic control of the alkane utilization phenotype in P. putida and P. aeruginosa involving at least six separate genes.